PENGGUNAAN MODEL PROBLEM BASED LEARNING PADA MATA PELAJARAN FIKIH DI KELAS VIII MTs M. BASIUNI IMRAN SAMBAS TAHUN PELAJARAN 2024/2025 - Rena Safitri; Oskar Hutaguluh; Ahmad Rathomi (CV. ADIBA AISHA AMIRA, 2025)
This study aims to reveal: 1) the use of the Problem-Based Learning Model in Fiqh (Islamic Jurisprudence) in eighth grade students at MTs. M. Basiuni Imran Sambas in the 2024-2025 academic year; 2) the supporting and inhibiting factors for the use of problem-based learning in Fiqh. This study employed a qualitative approach and field research. Data collection techniques included interviews, observation, and documentation. Data analysis techniques included data reduction, data presentation, conclusions, and verification. Source triangulation and member checking were used to verify data validity. Based on the data analysis, the results of this study indicate that: (1) Teachers have systematically implemented the PBL model through five stages: contextual problem orientation, learning group organization, independent or group investigation, solution development and presentation, and learning evaluation and reflection. (2) Supporting factors for the use of the PBL model in Fiqh learning include adequate learning facilities, curriculum-aligned teaching materials, and the teacher's ability to design interactive learning. Meanwhile, inhibiting factors include differences in student understanding, time constraints, and large class sizes. These findings confirm that the success of PBL is greatly influenced by teacher preparedness, student conditions, and a supportive learning environment.